1996
DOI: 10.1002/(sici)1097-4598(199602)19:2<210::aid-mus13>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Case of the month: Isaacs' syndrome associated with chronic inflammatory demyelinating polyneuropathy

Abstract: We report the first case of Isaacs' syndrome in which an inflammatory demyelinating neuropathy was documented histologically. For 9 months, the patient developed slowly progressive weakness, muscle spasms and stiffness, fasciculations, and myokymia in the arms, which were unmodified by sleep. Nerve conduction studies showed multifocal motor conduction block, abnormal dispersion phenomenon, and abnormal sensory and mixed nerve conduction. Needle electromyogram showed continuous motor unit potentials at rest wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…It may also be associated with a persistent facial contraction and has been noted to be present for up to 19 years [9,23]. It has been reported with other masses including cerebellar astrocytoma, metastatic tumors and acoustic neuroma.…”
Section: Myokymiamentioning
confidence: 55%
“…It may also be associated with a persistent facial contraction and has been noted to be present for up to 19 years [9,23]. It has been reported with other masses including cerebellar astrocytoma, metastatic tumors and acoustic neuroma.…”
Section: Myokymiamentioning
confidence: 55%
“…IS can be seen in isolation or it can be associated with neoplastic and nonneoplastic processes. 92 Regarding the association of IS with various malignancies, our review showed that there were 14 cases (20% of all patients) in which malignancies were reported before and after the diagnosis of IS (Table 1). As expected, thymoma was the most common tumor reported (n = 7), followed by lymphoma (n = 3), sarcomatoid carcinoma (n = 1) (malignancy that has characteristics of both carcinoma and sarcoma and grows rapidly), spinal cord hemangioblastoma (n = 1), gastric cancer (n = 1), and small-cell carcinoma (n = 1) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…IS can be seen in isolation or it can be associated with neoplastic and nonneoplastic processes. 92 Regarding the association of IS with various malignancies, our review showed that there were 14 cases (20% of all patients) in which malignancies were reported before and after the diagnosis of IS 100 For more information, visit: http://www.prisma-statement.org/.…”
Section: Associated Malignancies and Nonneoplastic Syndromesmentioning
confidence: 99%
“…MMN patients with fasciculations and myokymia and with continuous motor unit activity have been reported . Widespread myokymia, Isaacs syndrome, and continuous motor unit activity have been reported in chronic inflammatory demyelinating polyradiculoneuropathy. In line with these findings, CFS in our patient is thought to be secondary to monofocal motor neuropathy of the median nerve.…”
Section: Discussionmentioning
confidence: 99%